Higher education retention in Ireland and Scotland : the role of admissions policies - Iannelli, Cristina; McMullin, Patricia; Smyth, Emer (Springer Nature, 2025)
This article provides new insights into the role played by higher education (HE) selection policies in influencing student retention by exploring drop-out patterns in Ireland and Scotland. The Irish and Scottish HE systems differ in relation to the emphasis placed on grades and subjects studied at school and to the degree of autonomy enjoyed by HE institutions in the student admissions process. We investigate whether these system differences matter for student retention using administrative data from national student records and logistic regression modelling. The findings show that in Ireland, HE students have higher chances of dropping out than in Scotland and there are inequalities in these chances among students from different social backgrounds. Moreover, the association between subject matching (but also school grades) and the chances of dropping-out is stronger in Ireland than in Scotland. We conclude that the tighter student selection criteria in Scotland improve retention and reduce social inequalities in drop-out rates. Moreover, admission criteria are found to be important not only to explain between-country differences in drop-out rates but also within-country differences among different HE institutions.